Methodological Principles of Management Psychology: the Law of Uncertainty of Response (or Pygmalion’s Law) - Halus, Oleksandr (Pedagogical Discourse, 2025)
The article analyzes the law of uncertainty of response (or Pygmalion’s Law), which, among other laws, constitutes the methodological foundations of management psychology. It is noted that the problem of the methodology of scientific research is relevant for any science, since its achievements are largely determined by the development of its own methodological apparatus. Based on the analysis of psychological and pedagogical sources on management, it was found that the law of uncertainty of response, also known as Pygmalion’s Law, states that people’s expectations can influence their behavior and achievements. This law can be considered as a kind of psychological phenomenon in which the expectations of one person regarding another can influence the behavior of this other person, as a result of which these expectations come true. Taking into account the law of uncertainty of response (or Pygmalion’s law) in the educational activities of educational institutions in the context of psychological approaches makes it possible to instill faith in students in their pursuit of excellence, personal and professional growth, and self-actualization. In the self-concept, psychologist Carl Rogers developed a theory of self-actualization and psychotherapy. He proposed the concept of self-identity, which includes self-esteem, self-awareness, and self-acceptance. Self-esteem is the assessment that a person makes of their own characteristics, skills, abilities, and achievements. The self-expectancy effect is important, where our expectations of outcomes affect our behavior, which in turn affects outcomes. If we expect a person to be successful in a certain area, we can treat them differently, provide more opportunities for development, and support and praise them for their successes. This can stimulate their development and increase their confidence in their own abilities, which in turn can lead to improved outcomes.